PENGARUH KEBERADAAN PELABUHAN TANJUNG INTAN CILACAP TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN CILACAP - Kristian Cahyandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2019)
The existence of the port is of high concern at the moment, in an effort to boost the competitiveness of regional and national economies. Indicator of a port is said to be good or growing is through the high economic activity of the port.The method used in this research is qualitative description, and analysis of decision making. The results of the study show that the economic policy of the Tanjung Intan port in Cilacap needs to be continuously improved to support the economic growth of Cilacap Regency.The way to do this is through regional economic development in the port area, by developing the agriculture, fisheries and industrial sectors. Other policies are to strengthen port logistics network connectivity to the whole area of Cilacap Regency by improving the quality of the connecting infrastructure, and by building terminals or warehouses for adequate goods.